Assessment of spatial implications of photovoltaics deployment policies in the Netherlands. (1st September 2022) - Quax, Robin; Londo, Marc; van Hooff, Wijnand; Kuijers, Taco; Witte, Jaap; van Sark, Wilfried; Sinke, Wim
Highlights: Spatially resolved solar-PV potential in the Netherlands is quantified. Total solar-PV potential substantially larger than current ambitions for 2050. Area on roofs can cover most of what is needed in a 2050 decarbonised energy system. Innovative PV application options offer substantial additional generation potential. Policy choices and availability of options will have strong impact on deployment. Abstract: Electricity generation with photovoltaic (PV) solar energy technology requires significant amounts of space; a particular point of discussion in a densely populated country like the Netherlands. Therefore, we developed a new analytical framework to analyse potential electricity generation for specific PV typologies on 43 different land utilisation and water types. Our results indicate that spatial potentials for PV are substantial compared to current Dutch scenarios and ambitions for its role in a long-term decarbonised energy economy. The spatial potential of PV on rooftop areas is sufficient to largely meet these ambitions; however spatial allocation depends on more factors than the potential alone, e.g. desired implementation speed. Therefore, we have sketched some variants with a more balanced allocation over the various land use types. Innovative options, such as PV within offshore wind parks and on infrastructure, parking spaces and façades offer considerable opportunities for additional generation. Furthermore, we illustrate the considerable impacts on PV potential of (i) current net metering policy, (ii) the upcoming societal preference for lower panel densities in land-based PV parks, and (iii) a focus on cost efficiency instead of spatial efficiency. Policy makers should bear these outcomes in mind when designing support schemes for PV.